A Self‐Powered Lantern Based on a Triboelectric–Photovoltaic Hybrid Nanogenerator. Issue 4 (8th February 2018) - Cao, Ran; Wang, Jiaona; Xing, Yi; Song, Weixing; Li, Nianwu; Zhao, Shuyu; Zhang, Chi; Li, Congju
Abstract: The solar cell is widely used to convert sunlight into electric energy. However, its ability in harvesting energy is limited because it exclusively depends on sunlight. Inspired by a lantern swaying in the wind, triboelectric nanogenerator (TENG) is introduced to fabricate a triboelectric–photovoltaic hybrid nanogenerator, which is capable of harvesting both wind and solar energy with high efficiency. Moreover, a soft lithium battery (SLB) with designable shape and high capacity is adapted to instantly store the electric energy and guarantee stable output for the light‐emitting diodes inside the lantern. The hybrid nanogenerator exhibits high performance with a short‐circuit current about 150 µA at the rotation speed of 200 rpm and light intensity of 2 mW, illustrating the additive effect of the TENG and dye‐sensitized solar cells (DSSCs). Besides, after being charged by the hybrid nanogenerator for 0.88 h, the following discharge of the SLB at 10 µA can last 4.12 h, which is much longer compared with each component. The high integration of the TENG, DSSC, and SLB successfully makes a self‐powered lantern reality, which is a further step for multiple energy harvesting and self‐powered systems. Abstract : A self‐powered lantern is fabricated by integrating a triboelectric–photovoltaic hybrid nanogenerator together with soft lithium battery. The hybrid energy system is able to convert wind energy and solar energy simultaneously or individually, which promises a highly efficient utilization of the natural energy resource.